Comparative Tandem Mass Tag-Based Quantitative Proteomic Analysis of Tachaea chinensis Isopod During Parasitism - Li, Yingdong; Li, Xin; Han, Zhibin; Xu, Weibin; Li, Xiaodong; Chen, Qijun (Frontiers in Cellular and Infection Microbiology, 2019)
Parasitic isopods perforate and attach to the host integument via the mandibles and then feed on hemolymph and exudate from the wounds. Such isopods attack a variety of commercially important fish and crustacean hosts. Similar to other hematophagous parasites, isopods may also employ biomolecules that affect host blood conglutination and defense systems. In the present study, a tandem mass tag-based quantitative proteomic approach was used to identify differentially expressed proteins in Tachaea chinensis parasites of shrimp, by comparing parasitic (fed) and pre-parasitic (unfed) individuals. We identified 888 proteins from a total of 1,510 peptides, with a significant difference in 129 between the fed and unfed groups. Among these, 37 were upregulated and 92 were downregulated in unfed T. chinensis. This indicates that T. chinensis may require more energy before parasitism during its search for a host. In addition, as is the case for other blood-sucking parasites, it might secrete antihemostatic, anti-inflammatory, and immunomodulatory molecules to facilitate blood meal acquisition. To our knowledge, this study is the first to use a TMT-based proteomic approach to analyze the proteome of isopod parasites, and the results will facilitate our understanding of the molecular mechanisms of isopod parasitism on crustaceans.